A linear and efficient Doherty PA at 3,5GHz - Musolff, Christian; Kamper, Michael; Abou-Chahine, Zeid; Fischer, Georg (IEEE Microwave Magazine, 2013)
elib2cris::1512001600,musolff2013
Keywords: power amplifier; Doherty; load modulation; linearity; IMD; cancellation; 3; 5GHz; efficiency; backoff; twotone; harmonic balance

Comparison of class A and class D RF amplifier operation with focus on reverse intermodulation and efficiency performance - Kamper, Michael; Ulbricht, Gerald; Weigel, Robert; Fischer, Georg (European Microwave Integrated Circuits Conference, 2011)
A Current Mode Class D (CMCD) power amplifier at 900 MHz is presented. After a theoretical analysis, a class D amplifier is designed, simulated and afterwards assembled and characterized. Thereby, a maximum drain efficiency of 80.6%, and a maximum power added efficiency (PAE) of 72.8% at a switching frequency of 864 MHz, and an output power of 28.2 dBm were obtained. A linear class A amplifier using the same transistor exhibits a drain efficiency of 48.9% and 48.0% PAE at a comparable output power. An analysis of the reverse intermodulation distortion (IMD) of the switched-mode class D amplifier in comparison to the class A amplifier shows a 15dB improvement of the third order intermodulation ratio. To the authors' knowledge, this is the first practical verification of the superior reverse intermodulation performance of switched-mode amplifiers.
elib2cris::1512001600,kamper2011
Keywords: UHF power amplifiers; current-mode circuits; intermodulation distortion; radiofrequency amplifiers; current mode class D power amplifier; reverse intermodulation distortion

Effiziente HF Leisungsverstaerker mit geschalteten Transistoren - Kamper, Michael (Electrical and Electronic Engineering for Communication Workshop - Entwicklerforum - Fachmesse, 2012)
elib2cris::1512001600,kamper2012

Klasse-E Leistungsverstärker mit Lastmodulation - Lautenbacher, Thomas; Schmidt, Christian; Fehr, Matthias; Kamper, Michael; Weigel, Robert; Fischer, Georg; Kölpin, Alexander (EEEfCOM 2012, 2012)
elib2cris::1512001600,lautenbacher2012a

Linear and efficient Doherty PA Revisited - Musolff, Christian; Kamper, Michael; Abou-Chahine, Zeid; Fischer, Georg (IEEE Microwave Magazine, 2014)
elib2cris::1512001600,musolff2014
Keywords: power amplifier; doherty; linear; 3.5GHz; IMD; RFPA; PA; student design competition

Linear Doherty PA at 5 GHz - Musolff, Christian; Kamper, Michael; Fischer, Georg (IEEE Microwave Magazine, 2015)

Optimized output baluns for wideband differential class D PAs - Kamper, Michael; Fischer, Georg (2017 IEEE Topical Conference on Power Amplifiers for Wireless and Radio Applications, PAWR 2017, 2017)